Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Pada Pokok Bahasan Termokimia untuk Kelas XI SMA/MA - Rendra wijaya; Herdini Herdini; Abdullah Abdullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Abstract: This Research aims to develop Student Worksheet Based on Problem Based Learning in Thermochemistry of Chemistry in Senior High School Subject in terms of valid based on the feasibility aspect of content, characteristics of problem based learning, serve, language, and graphic. This type of research is research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student worksheet based on problem based learning. Instrument of data collection are validation and data collection technique given by three validators. Analysis of data obtained by the validity of aspect of content is 91.67% with valid category, the validity of characteristics of problem based learning is 96.67 with valid category, aspect of serve is 91,67% with valid category, the validity of aspect of language is 83,33% with valid category and validity of aspect of graphic is 89,58% with valid category. Based on the results of data analysis can be concluded that student worksheet based on problem based learning declared valid and can be used in Senior High School.